Presumed bilateral branch retinal vein occlusions secondary to antiepileptic agents - Hussain RN (Dove Medical Press, 2011)
Rumana N Hussain, Somnath BanerjeeLeicester Royal Infirmary, Leicester, UKAbstract: A 61-year-old man presented to the ophthalmology department having developed bilateral branch retinal vein occlusions. Baseline blood tests revealed no abnormality; however, subsequent investigations showed a raised plasma homocysteine (HC) level. The patient has been treated for refractory epilepsy for a number of years. Although antiepileptic medications have been shown to reduce folate levels and result in a raised HC level, this has not previously been shown to be to a level causing a retinal vascular event.Keywords: homocysteine, branch vein occlusions